PERILAKU BERKUBANG BADAK JAWA [Rhinoceros sondaicus] DI TAMAN NASIONAL UJUNG KULON - Nicanor J.V. Siterus; Yanto Santosa; Abdul Haris Mustrai (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
As one of the very rare and critically endangered species, Javan rhinoceros currently has a population of around 40-50 heads and can only be found in Ujung Kulon National Park. However, these numbers are still questionable due to the lack of description provided by the existing methods in estimating the entire population of Javan rhinoceros in the Ujung Kulon peninsula. The Javan rhinoceros timid nature, high alertness, and tendency to avoid direct contact with human and other wildlife are the factors that complicate the estimation of population. These factors make the Javan rhinoceros difficult to find and to track. One method that can be used is the video trap data analysis method. The objective of this research was to obtain information on the time and duration of Javan rhinoceros wallowing activities, the patterns and mechanisms of Javan rhinoceros wallowing activities, and the types of activity of Javan rhinoceros during wallowing. Keywords : Javan rhinoceros, wallowing behavior